Analisis Kualitas Produk Dan Kualitas Pelayanan Terhdap Kepuasan Pelanggan Pada Usaha Gethuk Goreng Frozen Di Toko Bu Slameto Depok 2 - Andriyani, Margaretha; I Gusti Ayu Ngurah; Rina Febriana (Program Studi Tata Boga Universitas Negeri Jakarta, 2023)
The aims of this study are: 1) to determine whether service quality has a significant effect on customers’ satisfaction at Toko Bu Slameto, 2) to determine whether product quality has a significant effect on customers’ satisfaction at Toko Bu Slameto, 3) to determine whether price has a significant effect on customers’ satisfaction at Toko Bu Slameto, 4) to determine whether product packaging has a significant effect on customers’ satisfaction at Toko Bu Slameto, 5) to determine whether taste innovation has a significant effect on customers’ satisfaction at Toko Bu Slameto, and 6) to determine whether ease-of-order has a significant effect on customers’ satisfaction at Toko Bu Slameto. This research was carried out at Toko Bu Slameto Depok 2 from March 2021 to January 2022. This is a descriptive qualitative research using the survey method. The research sample is 30 respondents who have purchased Bu Slameto’s frozen gethuk goreng more than once. Analyzing the result shows that the customers’ satisfaction level is adequate in service quality, product quality, and price aspects of the frozen gethuk goreng Toko Bu Slameto. Hypothesis testing results show: 1) service quality has a significant effect on consumers’ satisfaction (73%), 2) product quality has a significant effect on consumers’ satisfaction (81%), 3) price has a significant effect on consumers’ satisfaction (63,3%), 4) product packaging does not affect consumers’ satisfaction significantly (58%), 5) taste innovation has a significant effect on consumers’ satisfaction (90%), and 6) ease-of-order has a significant effect on consumers’ satisfaction (87%).